Efficacy of natural products against tea mosquito bug (Helopeltis spp.) in cashew (Anacardium occidentale) based farming system - NISHA LEKSHMI V; MEERA MANJUSHA A V (The Indian Journal of Agricultural Sciences)
The cashew tree (Anacardium occidentale L.) is a vital crop in tropical regions, yet its production and productivity are hindered due to pest infestation, particularly by the tea mosquito bug (TMB) (Helopeltis spp.), causing substantial yield losses. The present study was carried out during 2019–2023 at Kerala Agricultural University, Regional Agricultural Research Station, Pilicode, Kasaragod, Kerala to evaluate the effectiveness of various botanical and natural products in managing TMB infestation in cashew. The variety selected for the study was Madakkathara. The experiment was laid out in a randomized block design (RBD), with three replications. Present study was part of the entomological trials of All India Coordinated Research Programme (AICRP) on cashew, wherein, the efficacy of Neem Seed Kernel Extract (NSKE), Kasaragod Dwarf Cows’ Urine and several plant leaf extracts were tested against TMB, comparing their results with the standard chemical control (Lambda-cyhalothrin). The results of the study suggested that natural products like neem seed kernel extract can be utilized as an alternative for TMB management in cashew plantations promoting a sustainable and eco-friendly pest management approach without adversely affecting the environment.